Association of AMPA Receptors with a Subset of Glutamate Receptor-Interacting Protein In Vivo - Wyszynski, Michael (J Neurosci, 1999)
The NMDA and AMPA classes of ionotropic glutamate receptors are concentrated at postsynaptic sites in excitatory synapses. NMDA receptors interact via their NR2 subunits with PSD-95/SAP90 family proteins, whereas AMPA receptors bind via their GluR2/3 subunits to glutamate receptor-interacting protein (GRIP), AMPA receptor-binding protein (ABP), and protein interacting with C kinase 1 (PICK1). We report here a novel cDNA (termed ABP-L/GRIP2) that is virtually identical to ABP except for additional GRIP-like sequences at the N-terminal and C-terminal ends. Like GRIP (which we now term GRIP1), ABP-L/GRIP2 contains a seventh PDZ domain at its C terminus. Using antibodies that recognize both these proteins, we examined the subcellular localization of GRIP1 and ABP-L/GRIP2 (collectively termed GRIP) and their biochemical association with AMPA receptors. Immunogold electron microscopy revealed the presence of GRIP at excitatory synapses and also at nonsynaptic membranes and within intracellular compartments. The association of native GRIP and AMPA receptors was confirmed biochemically by coimmunoprecipitation from rat brain extracts. A majority of detergent-extractable GluR2/3 was complexed with GRIP in the brain. However, only approximately half of GRIP was associated with AMPA receptors. Unexpectedly, immunocytochemistry of cultured hippocampal neurons and rat brain at the light microscopic level showed enrichment of GRIP in GABAergic neurons and in GABAergic nerve terminals. Thus GRIP is associated with inhibitory as well as excitatory synapses. Collectively, these findings support a role for GRIP in the synaptic anchoring of AMPA receptors but also suggest that GRIP has additional functions unrelated to the binding of AMPA receptors.